Competency-Based Learning and Learning Situations - Velasco Fernández, África; Conde Lanchazo, José Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2025)
This article examines competence-based learning and learning situations as key approaches in the transformation of teaching practice. It outlines the process of designing such situations and traces their evolution from the traditional model of didactic units, driven by educational reforms that prioritise a student-centred approach. The benefits of this model are highlighted, particularly its promotion of active learning based on experience, reflection, and the application of knowledge and skills in real-life contexts—making education more meaningful and relevant for both teachers and students. It is important to emphasise that everything discussed regarding the various learning situations is a direct reflection of classroom practice.
Keywords: learning situation; didactic unit; LOE; LOMCE; LOMLOE; learning competences; reality; life; reflection; active learning; experiences; application; meaningful learning